2021
DOI: 10.1101/2021.01.06.425648
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human B cell lineages engaged by germinal centers following influenza vaccination are measurably evolving

Abstract: Poor efficacy of seasonal influenza virus vaccines is often attributed to pre-existing immunity interfering with the persistence and maturation of vaccine-induced B cell responses.1 Consistent with this notion, no significant increase in somatic hypermutation (SHM) among circulating influenza-binding lineages was detected following seasonal vaccination in humans.2 A more recent study showed that at least a subset of vaccine-induced B cell lineages are recruited into germinal centers (GCs) following vaccination… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…We found one lineage, which possesses all features of HBmem cluster except one monophyletic clade, typical for LBmem lineage, thus at least some of LBmem clonal lineages represent progeny of reactivated persistent memory B cells, represented among HBmem lineages. This example of HBmem-LBmem transition is very similar to reactivated persistent memory, observed by Hoehn et al in response to seasonal flu vaccination (Hoehn et al 2021).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We found one lineage, which possesses all features of HBmem cluster except one monophyletic clade, typical for LBmem lineage, thus at least some of LBmem clonal lineages represent progeny of reactivated persistent memory B cells, represented among HBmem lineages. This example of HBmem-LBmem transition is very similar to reactivated persistent memory, observed by Hoehn et al in response to seasonal flu vaccination (Hoehn et al 2021).…”
Section: Discussionsupporting
confidence: 83%
“…Persisting clonal lineages which predominantly were represented by the cells with IgM/IgD isotypes and demonstrated signs of neutral evolution were recently reported (Horns et al 2019). Concordantly, Hoehn and colleagues showed reactivation of clonal lineages after seasonal influenza vaccination (Hoehn et al 2021).…”
Section: Introductionmentioning
confidence: 83%
“…However, the role of the GC response in the human B cell response to vaccination was until recently unclear owing to an inability to directly sample draining lymph nodes following vaccination. We used ultrasound-guided fine needle aspiration to serially sample the draining lymph node following influenza vaccination and found that vaccination induced a robust GC response in which B cells undergo somatic hypermutation 95 , 96 . We then used this approach to assess the B cell response in the draining axillary draining lymph nodes of individuals who received the Pfizer–BioNTech SARS-CoV-2 vaccine 97 .…”
Section: B Cell Response To Sars-cov-2 Vaccinationmentioning
confidence: 99%
“…It is unknown to which extent vaccination against H1N1pmd09 induces affinity maturation in HSCT patients and it is currently under debate whether poor vaccine-induced affinity maturation is responsible for the poor effectiveness of seasonal influenza vaccines [38][39][40]. Previous studies in healthy adults showed that serum avidity against HA1 peaks at 21-28d after vaccination and decreases almost back to baseline on d180 [25,41].…”
Section: Plos Pathogensmentioning
confidence: 99%